Economic value added or earnings: What explains market value in Indian firms? - Nufazil Altaf (Future Business Journal, 2016)
The purpose of this paper is to empirically test the claim made by Stern Stewart & Company that economic value added is a better metric that traditional earning based measures in explaining market value. For better exposition, a sample of 325 Indian firms has been divided into two parts- 170 firms belonging to Indian manufacturing companies and 155 companies belonging to the Indian service sector. After performing univariate and multivariate regression analyses, the results of the study reveal that the operating income has a strong linkage with market value added in both manufacturing and service sectors. For both the sectors, the economic value added shows weaker but positive relationship with the market value added.
Keywords: 650